Pasteurellosis among breeding Eiders Somateria mollissima in the Netherlands - Swennen, C; Smit, Th (Wildfowl, 1991)
A section of the Eider colony on Vlieland lost a significant proportion of its breeding females through pasteurellosis in May 1984. The nesting density and, especially, the age composition in this section were still affected five years after the incident.